2011
DOI: 10.1111/j.1439-0418.2010.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour of the greenbug Schizaphis graminum on wheat plants treated with imidacloprid and/or silicon

Abstract: The greenbug Schizaphis graminum (Rond.) (Hemiptera: Aphididae) is one of the principal pests of Triticum aestivum L. and may be responsible for the injection of toxins, the transmission of viral infections and, ultimately, plant death. The aphid can be controlled by the use of selective insecticides or with the application of silicon. The objective of the present study was to investigate the influence of imidacloprid and silicon on the feeding behaviour of S. graminum on wheat plants. Aphids collected from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…For the aphids that did not achieve xylem ingestion, it is possible that a small amount of insecticide may be present in the phloem sap, resulting in reduced feeding (Nauen and Elbert 1994). Our Þndings are supported by the work of Costa et al (2011), who observed similar feeding behavior in greenbugs, Schizaphis graminum Rondani, exposed to imidacloprid-treated wheat seed. Greenbugs exposed to treated plants exhibited signiÞcantly less phloem ingestion.…”
Section: Table 2 Mean Number Of Soybean Aphids (؎ Sem) For Thiamethosupporting
confidence: 88%
See 1 more Smart Citation
“…For the aphids that did not achieve xylem ingestion, it is possible that a small amount of insecticide may be present in the phloem sap, resulting in reduced feeding (Nauen and Elbert 1994). Our Þndings are supported by the work of Costa et al (2011), who observed similar feeding behavior in greenbugs, Schizaphis graminum Rondani, exposed to imidacloprid-treated wheat seed. Greenbugs exposed to treated plants exhibited signiÞcantly less phloem ingestion.…”
Section: Table 2 Mean Number Of Soybean Aphids (؎ Sem) For Thiamethosupporting
confidence: 88%
“…Greenbugs exposed to treated plants exhibited signiÞcantly less phloem ingestion. Unlike our study, feeding was affected within 8 h of imidacloprid exposure (Costa et al 2011). …”
Section: Table 2 Mean Number Of Soybean Aphids (؎ Sem) For Thiamethomentioning
confidence: 78%
“…Silicon promoted cuticle thickening and accumulation of crystals on the leaf stomata in sugarcane [54]. The action of silicon may not be only restricted to resistance constitutive or induced but may also involve induced plant chemical defense [51].…”
Section: Activity On Insect Stage Treatment (Concentration or Dose) [mentioning
confidence: 99%
“…Mortality on egg (90-100%) Gamma irradiation (200 Gy) [45] essential nutritional element to the plants [49], but as potassium silicate, calcium silicate, and sodium silicate from other sources has determined the tolerance of many plant species to insects [50][51][52][53]. Silicon promoted cuticle thickening and accumulation of crystals on the leaf stomata in sugarcane [54].…”
Section: Activity On Insect Stage Treatment (Concentration or Dose) [mentioning
confidence: 99%
“…Positive effects on the use of Si are evident in the reduction of feeding time of the aphid Schizaphis graminum (Rondani) (Hemiptera: Aphididae) in wheat (Triticum aestivum L., Poaceae) [12], protection of cucumber plant (Cucumis sativa L., Cucurbitaceae), eggplant (Solanum melongena L., Solanaceae), common bean (Phaseolus vulgaris L., Fabaceae) and corn (Zea mays L., Poaceae) against the two-spotted spider mite, Tetranychus urticae Koch (Tetranychidae) [13] and reduced the palatability of sunflower leaves (Helianthus annuus L., Asteraceae) to the attack of caterpillar Chlosyne lacinia saundersii Doubleday (Lepidoptera: Nymphalidae) [14].…”
Section: Introductionmentioning
confidence: 99%